Bilateral Pheochromocytoma with a Novel Pathogenic Variant in the MAX Gene: A Case Report - Low, Chee Koon; Krishnabalan, Kausalyaa; Nasruddin, Azraai Bahari; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
Pheochromocytomas and paragangliomas syndrome are grouped into three specific disease clusters based on their underlying genetic alterations. Pathogenic variants affecting the myelocytomatosis-associated factor X (MAX) gene predispose pheochromocytomas and paragangliomas syndrome to occur at younger ages, with more than half having bilateral pheochromocytomas. We report a case of bilateral pheochromocytomas with a novel pathogenic variant identified in the MAX gene (c.234_235dup). This young male was found to have a huge left suprarenal mass after he presented with severe hypertension and myocardial infarction. His endocrine workup confirmed a diagnosis of pheochromocytoma as evidenced by elevated levels of normetanephrine, metanephrine, and 3-methoxytyramine in the urine. CT of the adrenal glands revealed bilateral adrenal masses; the widest diameter for the left adrenal mass was almost 8 cm whereas for the right one was 2 cm. 68Gallium-DOTATATE functional imaging showed significant uptake in the left adrenal mass, but indeterminate on the right, and no significant uptake was seen elsewhere to suggest metastatic lesions. He did not have syndromic features associated with multiple endocrine neoplasia, neurofibromatosis or von Hippel Lindau disease. The collective findings raised the clinical dilemma of whether unilateral or bilateral adrenalectomy should be pursued. The detection of pathogenic MAX gene was therefore crucial in guiding personalized treatment strategy. Following the bilateral adrenalectomy, his hypertension was cured. Annual biochemical screening and 2-yearly MRI imaging to look for recurrence of pheochromocytomas were planned according to international consensus.